Perhitungan dan Penggunaan Parameter Pertumbuhan Serangga dalam Pengujian Senyawa Penghambat Pertumbuhan Serangga - Agus Dana Permana (Jurnal Perlindungan Tanaman Indonesia, 1999)
Studies of the effect of allelochemicals or other insect growth regulator on the development of insect is difficult using parameter currently employed. By measuring the effect growth inhibiting of seed crude extract of soursop seed, (Annona muricata); neem seed, (Azadirachta indica); and leaf crude extract of Lantana, (Lantana camara) on the Heliothis armigera larvae, growth index (GI) and relative growth index (RGI) calculation are demonstrated in this paper.